Sejarah Gerakan Politik Pemuda di Jakarta Sekitar Proklamasi - Utomo, Satriono Priyo (Universitas Indraprasta PGRI, 2021)
The history of the Indonesian youth political movement in 1928 not only inherited national politics with the ties of